Validity and Reliability Test Of A Written English Test Online-Based Using Google Form - Iin Mutmainah; Ary Fadjar Isdiati (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The purpose of this research are (1) to produce an online-based English test and (2) to determine the validity and reliability of the online-based written English test with using Google Form. Writing is a key element of communication and a critical part of comprehension. This research used quantitative descriptive analysis as a method research design. The instrument used is an instrument developed online, through the expert validation instrument data analysis, analysis of assessment data and student responses to tests, and instrument trial. The development of an online-based written English test using Google Form is expected to be able to measure the extent to which a student's ability to the material has been taught. Then, the result of validity test were counted by using Pearson Product Moment. The result of this research is a software product in the form of a website which includes a discussion of each indicator and fulfills the requirements eligibility criteria, there are 8 categories of questions that are not valid from 40 multiple choice questions and has been tested on a limited basis, and the product has been well received by students when trials.